1 William E. Miller, Revised and Annotated Code of Iowa 265 (1880) - (:unkn) unknown (My University, 1880)
Title 8, Ch. 1, § 36 Unlawful for Other than Regularly Organized Militia to Organize: Prohibited any body of men, other than the regularly organized volunteer militia and federal troops, from associating as a military company or to drill or parade.
Keywords: MILITIAS